42.2k views
3 votes
Correctly factor the expression 15a-6b+36 using the greatest common factors

2 Answers

5 votes

Answer:

3 ( 5a - 2b + 12)

Explanation:

15 = 3 * 5

6 = 2 * 3

36 = 2 * 2 * 3 * 3

GCF = 3

15a - 6b + 36 = (3* 5 * a) - (3 *2 * b) + (3 * 12)

= 3 ( 5a - 2b + 12)

User Manvi
by
5.8k points
1 vote

Answer:

3 ( 5a - 2b + 12)

Explanation:

15 = 3 * 5

6 = 2 * 3

36 = 2 * 2 * 3 * 3

GCF = 3

15a - 6b + 36 = (3* 5 * a) - (3 *2 * b) + (3 * 12)

= 3 ( 5a - 2b + 12)

User Kirk Roybal
by
6.6k points